(untitled) (CIPEEX, 2025)
The pandemic context caused by COVID-19 has resulted in numerous challenges across various sectors, including higher education. The impact on the academic formation of students who began their undergraduate studies between 2019 and 2020 has become a topic of increasing concern and debate. During the first semesters, which are considered essential for building academic and social foundations, these students faced the abrupt transition to online learning. This study explores the consequences of this shift on the development of academic and interpersonal skills, examining the intersection between psychological and sociological factors. The research focuses on the challenges faced by these students as they approach the final stages of their degrees, analyzing how the lack of in-person interaction and adaptation to the digital format have influenced their academic trajectories. The article aims to contribute to the understanding of the long-term implications of this experience, offering valuable insights for the formulation of educational policies and support strategies in higher education.